From landscape to the city (2003)
The present text is made up of two thematic blocks, being a first of them the dissertation around the landscape, to its definition and nature as much as to its relation with the enviroment. Once established the dimension of the most recent and more complete landscape, they are approached, in the second block, its specific nexuses with the city, treating in this case of extending, until now, habitual form to tipify the applications of landscape in the city.